2021
DOI: 10.1016/j.jiac.2020.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of blood urea nitrogen and the neutrophil-to-lymphocyte ratio as predictors of mortality among elderly patients with genitourinary tract infections: A retrospective multicentre study

Abstract: Objectives: To investigate whether initial blood urea nitrogen (BUN) and the neutrophil-to-lymphocyte ratio (NLR) in the emergency department (ED) are associated with mortality in elderly patients with genitourinary tract infections. Methods: A total of 541 patients with genitourinary tract infections in 5 EDs between November 2016 and February 2017 were included and retrospectively reviewed. We assessed age, sex, comorbidities, vital signs, and initial laboratory results, including BUN, NLR and the SOFA crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…NLR could also be used as a prognostic marker in various diseases (including pulmonary embolism, pancreatitis, sepsis, etc. ), and some studies have demonstrated a linear relationship [13][14][15][16][17]24]. Other studies have demonstrated J-shaped relationships of NLR and cortisol levels with patient survival [18,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NLR could also be used as a prognostic marker in various diseases (including pulmonary embolism, pancreatitis, sepsis, etc. ), and some studies have demonstrated a linear relationship [13][14][15][16][17]24]. Other studies have demonstrated J-shaped relationships of NLR and cortisol levels with patient survival [18,37].…”
Section: Discussionmentioning
confidence: 99%
“…It is a surrogate marker of systemic response to physiological stress. NLR is associated with adverse outcomes in many diseases [13][14][15][16][17][18][19] and can help in early predicting AKI [20][21][22]. In a study of 10,859 patients admitted to an intensive care unit (ICU), Zheng et al [23] noted that platelet-to-lymphocyte ratio, an inflammatory marker similar to NLR, exhibited a U-shaped relationship with mortality in patients with critical illness and AKI.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the NLR ≥ 23.8 predicted all resulted in death at elderly UTI patient, with the sensitivity of 38% and specificity about 88%. When the BUN and NLR were combined with MAP for mortality prediction, the sensitivity was equivalent to Sequential organ failure asessment score (SOFA) at 87.5%, and the specificity was 61% greater than SOFA [24].…”
Section: Nlr and Plr In Urinary Tract Infectionmentioning
confidence: 99%
“…4 Rasio Neutrofil Limfosit (RNL) adalah indikator sederhana yang mudah diakses hanya dengan melihat hasil hitung darah lengkap dan menggambarkan status inflamasi sistemik pasien. 5 Hitung darah lengkap selalu dilakukan pada seseorang yang dirawat inap di rumah sakit. Salah satu reaksi fisiologis sistem imunitas terhadap inflamasi sistemik adalah peningkatan jumlah neutrofil dan penurunan jumlah limfosit.…”
Section: Pendahuluanunclassified